WOMEN'S BODY IMAGE SELF-CONSCIOUSNESS DURING INTIMACY WITH A PARTNER (BISC-UA): UKRAINIAN-LANGUAGE ADAPTATION OF THE SCALE - Zavada, Tetiana; Shyroka, Anastasia (Psychological Prospects Journal, 2022)
Purpose. Body image self-consciousness in the intimacy relationships is important aspect of women’s sexuality, related to the women’s ability to get satisfaction in sexual relationships. This is one of the main indicators of the healthy sexual relations, which can be evaluated with psychodiagnostic instruments. However, there are no valid and reliable tools for the assessment of the phenomena in Ukrainian psychology.  Thus, the aim of the study was to translate and adapt Wiederman’s Body Image Self-Consciousness (BISC) Scale into Ukrainian. Such psychometric properties were under consideration: scale’s items distribution, scale’s factor structure, internal consistency, test-retest reliability and convergent validity.  Methods: The research was conducted among women (N=731), aged 18-21. 37 women took part in the test-retest evaluation during the 5th-week period. BISC-UA scale сonvergent validity was determined in comparison with the constructs of body image satisfaction and psychological tendencies in sexual relationships, using The Body Areas Satisfaction Scale (Giovannelli et al., 2008), Body Image Questionnaire (Skugarevsky, Sivukha), and the Multidimensional Sexuality Questionnaire (Ukrainian-language adaptation by Shyroka, Zavada, 2022).Results. Considering the indicators of asymmetry and excess, most statements have a normal distribution with slight left asymmetry. The results of exploratory and confirmatory factor analysis confirms that BISC-UA scale is  one-factor instrument, which consists of 15 items (RMSEA=0.00, RMR = 0.086, GFI= 0.996, NFI=0.994, CFI=1.00, N=731).  The scale has excellent coefficients of internal consistency (Cronbach’s Alpha  0,95, McDonald’s Omega 0,96). The Scale demonstrates an appropriate level of test-retest reliability during the 5th week period (r=0,72) and convergent validity compared with given constructs of body image satisfaction and psychological tendencies in sexual relationships.Conclusions. The Ukrainian-language Body Image Self-Consciousness Scale in the intimacy relationships (BISC-UA) has appropriate psychometric properties and can be recommended for use in research on the quality of women’s sexual life.